Effect on thermoregulatory responses in patients undergoing a tympanoplasty in accordance to the anesthetic techniques during PEEP: a comparison between inhalation anesthesia with desflurane and TIVA - Ki Tae Jung; Sang Hun Kim; Hyun Young Lee; Jong Dal Jung; Byung Sik Yu; Kyung Joon Lim; Keum Young So; Ju Young Lee; Tae Hun An (Korean Journal of Anesthesiology, 2014)
BackgroundIt has been known that positive end-expiratory pressure (PEEP) increases the vasoconstriction threshold by baroreceptor unloading. We compared the effect on the thermoregulatory responses according to anesthetic techniques between an inhalation anesthesia with desflurane and a total intravenous anesthesia (TIVA) with propofol and reminfentanil when PEEP was applied in patients undergoing tympanoplasty.MethodsForty-six patients with a scheduled tympanoplasty were enrolled and the patients were divided in two study groups. Desflurane was used as an inhalation anesthetic in group 1 (n = 22), while TIVA with propofol and remifentanil was used in group 2 (n = 24). PEEP was applied by 5 cmH2O in both groups and an ambient temperature was maintained at 22-24℃ during surgery. The core temperature and the difference of skin temperature between forearm and fingertip were monitored for about 180 minutes before and after the induction of general anesthesia.ResultsThe final core temperature was significantly higher in group 2 (35.4 ± 0.7℃) than in group 1 (34.9 ± 0.5℃). Peripheral thermoregulatory vasoconstriction was found in 5 subjects (23%) in group 1 and in 21 subjects (88%) in group 2. The time taken for reaching the thermoregulatory vasoconstriction threshold was 151.4 ± 19.7 minutes in group 1 and 88.9 ± 14.4 minutes in group 2.ConclusionsWhen PEEP will be applied, anesthesia with TIVA may have more advantages in core temperature preservation than an inhalation anesthesia with desflurane.